Lack of multidrug resistance-associated protein 4 (Mrp4) alters the kinetics of acetaminophen toxicity. (2019) - Donepudi, Ajay C; Goedken, Michael J.; Schuetz, John D.; E Manautou, José
Abstract: Acetaminophen (APAP) overdose is the most frequent cause of drug-induced liver injury in humans and a common chemical model to investigate genetic determinants of susceptibility to drug-induced liver injury (DILI). Previous studies performed in our laboratory identified the efflux transporter multidrug resistance-associated protein 4 (Mrp4) as an inducible gene in the liver following toxic APAP exposure in both humans and rodents. In mice, blockade of hepatic Mrp4 induction following APAP administration increases susceptibility towards APAP hepatotoxicity. Collectively, these findings suggest that Mrp4 plays an important role in tolerance to APAP-induced liver injury. To further study the role of Mrp4 in APAP-induced hepatotoxicity, we treated 10–12 weeks old male wild type (WT, C57BL/6J) and Mrp4 knockout (Mrp4 −/− ) mice with APAP (400 mg/Kg in saline, i.p. ) or vehicle. Liver injury endpoints and hepatic gene expression were analyzed at 12, 24 and 48 h post-APAP injections. Unexpectedly, the kinetics of histologically measured liver damage and plasma ALT revealed that Mrp4 −/ mice had decreased ALT levels and hepatic necrosis compared to WT mice only at 12 h. Notably, hepatic non-protein sulfhydryl (NPSH) levels were increased in the APAP treated Mrp4 −/− mice at intervals less than 24 h, consistent with the capability of Mrp4 to export glutathione. Further gene expression analysis revealed that hepatic drug metabolism genes were downregulated in Mrp4 −/− mice at earlier time points post-APAP administration. However, despite significant decreases in endpoints of liver injury detected at an early time point after APAP treatment, these changes were not sustained at later time points as Mrp4 −/− mice ultimately had hepatic toxicity at levels comparable to WT mice. In conclusion, our data indicate that lack of Mrp4 by itself in mice does not alter susceptibility to APAP toxicity.